Návrh a implementace obchodního systému v prostředí devizových trhů - Toth, Václav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá návrhem automatického obchodního systému a jeho implementací v prostředí devizových trhů. Tento systém vznikne jako investiční model na základě provedených analýz a následně bude testován na reálných datech za účelem dosažení maximální stability a zisku.

The master thesis deals with proposal of automated trading system and its implementation in the Foreign exchange market environment. This system will be developed as investment model based on the analyzes performed and then tested on real data to achieve maximum stability and profit.
Proposal and Implementation of Business System in the Foreign Exchange Market Environment
Keywords: Finanční trhy; Forex; automatický obchodní systém; optimalizace; investiční strategie; MetaTrader 4; Larry Williams; vliv ceny zlata na devizové trhy.; Financial markets; Forex; automated traiding system; optimazation; investment strategy; MetaTrader 4; Larry Williams; influence of the price of gold on foreign exchange markets.